2019
DOI: 10.1002/zoo.21517
|View full text |Cite
|
Sign up to set email alerts
|

The addition of soil and chitin into Sunda pangolin (Manis javanica) diets affect digestibility, faecal scoring, mean retention time and body weight

Abstract: Pangolins (Manis spp.) are myrmecophagous mammals with a wild diet of termites and ants. Diets are not yet readily acceptable by all pangolins and lack soil and chitin compared to their wild diet. This study aimed to assess the usefulness of including soil and chitin in pangolin diets by measuring changes in digestibility, food mean retention time, faecal scoring and body weight changes.Two male and two female Sunda pangolins (Manis javanica) from Night Safari (Singapore) were fed their typical gruel-type diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Chitin is the main ingredient of the exoskeleton of P. dives. A recent study showed that adding 5% chitin into artificial food of Chinese pangolin could increase the apparent digestibility of fat by 3.5% but decreased the apparent digestibility of dry matter, crude F I G U R E 1 Colony members composition of Polyrhachis dives protein, ash, and energy by more than 10% (Cabana et al, 2017;Cabana & Tay, 2019;Lin et al, 2015;Zhang, 2004). Moreover, chitin added into the diet could shorten the period that food stayed in the digestive tract, allowing feces to be shaped into strips or lumps which were similar to the ones discovered in wild (Zhang, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitin is the main ingredient of the exoskeleton of P. dives. A recent study showed that adding 5% chitin into artificial food of Chinese pangolin could increase the apparent digestibility of fat by 3.5% but decreased the apparent digestibility of dry matter, crude F I G U R E 1 Colony members composition of Polyrhachis dives protein, ash, and energy by more than 10% (Cabana et al, 2017;Cabana & Tay, 2019;Lin et al, 2015;Zhang, 2004). Moreover, chitin added into the diet could shorten the period that food stayed in the digestive tract, allowing feces to be shaped into strips or lumps which were similar to the ones discovered in wild (Zhang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Chitin and formic acid were commonly found in ants, thus might play an important role in the Chinese pangolin diet. Some studies paid attention to the nutrition effect of chitin and add it to the diet of pangolin (Cabana et al, 2017; Cabana & Tay, 2019; Lin et al, 2015), but there is no reference on how much chitin should be added. As for formic acid, few artificial pangolin diets contain it because they overlooked its functions.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that adding chitin to the diet may be a practical method to control the weight of pangolins in captivity [ 39 ]. Cabana found that the addition of food containing more chitin to the pangolin’s diet may increase the average retention time of food in the pangolin stomach [ 52 ]. Therefore, adding chitin in the artificial diet might be beneficial for the gut health of pangolins partially due to the impact on digestibility.…”
Section: Other Factors Affecting the Nutrition Of Pangolinsmentioning
confidence: 99%
“…The echidna secures ants and termites using an elongated tongue that is moistened with sticky saliva; inadvertently inorganic matter such as soil and sand are ingested (Augee et al, 2006). The ingested soil and sand have an important role in the digestive process by assisting the tough cornified stomach in grinding invertebrate bodies (Augee et al, 2006) and has been shown to facilitate fecal formation in the numbat ( Myrmecobius fasciatus ; Power & Monaghan, 2003) and Sunda pangolin ( Manis javanica ; Cabana & Tay, 2020).…”
Section: Introductionmentioning
confidence: 99%